2011
DOI: 10.1057/ejis.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

Focus groups and critical social IS research: how the choice of method can promote emancipation of respondents and researchers

Abstract: Cindy, "Focus groups and critical social IS research: How the choice of method can promote emancipation of respondents and researchers" (2009).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 63 publications
0
69
0
Order By: Relevance
“…Papers removed from the list included papers that suggest future work should include focus groups, that were not IS-related, or papers that discussed focus groups as a method to be adapted for other purposes such as online market research (Clapper and Massey 1996;Markham et al 2006;Montoya-Weiss et al 1998) or for applicability checks (Glass 2009;Rosemann and Vessey 2008), discussed focus group as a research method (Sobreperez 2008;Stahl et al 2011), discussed focus group as a method for requirements determination in IS development (Leifer et al 1994;O'hEocha et al 2010;Peffers and Tuunanen 2005) or to inform design research (Tremblay et al 2010), or explored IS education issues using focus groups (Dunning et al 2001;Dwyer and Knapp 2004;Maheshwari et al 2009;Shuk Ying et al 2008). The resulting sample of 58 papers shows that the oldest papers date to 1995 and 1996 in MIS Quarterly (Lee et al 1995;Smith et al 1996), Information Systems Research (Manning 1996), and Information Technology and Libraries (Tillotson et al 1995).…”
Section: Literature Review: Focus Group Research In Ismentioning
confidence: 99%
“…Papers removed from the list included papers that suggest future work should include focus groups, that were not IS-related, or papers that discussed focus groups as a method to be adapted for other purposes such as online market research (Clapper and Massey 1996;Markham et al 2006;Montoya-Weiss et al 1998) or for applicability checks (Glass 2009;Rosemann and Vessey 2008), discussed focus group as a research method (Sobreperez 2008;Stahl et al 2011), discussed focus group as a method for requirements determination in IS development (Leifer et al 1994;O'hEocha et al 2010;Peffers and Tuunanen 2005) or to inform design research (Tremblay et al 2010), or explored IS education issues using focus groups (Dunning et al 2001;Dwyer and Knapp 2004;Maheshwari et al 2009;Shuk Ying et al 2008). The resulting sample of 58 papers shows that the oldest papers date to 1995 and 1996 in MIS Quarterly (Lee et al 1995;Smith et al 1996), Information Systems Research (Manning 1996), and Information Technology and Libraries (Tillotson et al 1995).…”
Section: Literature Review: Focus Group Research In Ismentioning
confidence: 99%
“…Focus groups are also used as a data collection method by researchers, mainly in social sciences [40]. Recently, focus groups have been used as a method in critical social information systems (IS) research [37]. Morgan [25] describes focus groups as group interviews.…”
Section: Research Approachmentioning
confidence: 99%
“…Stahl et al [37] note that focus groups, despite the long history in many fields, still is not an often used data collection method in IS research. However, focus groups have been used in several e-government projects to gather citizens' opinions of eservices [9; 10] before and during e-service development processes [e.g.…”
Section: Research Approachmentioning
confidence: 99%
“…Compared to other methods such as individual interviews and surveys, the interactive and synchronous group discussion aspect of focus groups allows participants to discuss, agree, or dissent with each other's ideas and to elaborate the opinions they have already mentioned. Therefore, the method not only helps one attain a deeper shared meaning of responses that enhances the trustworthiness of research results (Kitzinger, 1994;Stahl, Tremblay, & LeRouge, 2011) but also provides the unique opportunity to obtain rich group interaction data (Onwuegbuzie, Dickinson, Leech, & Zoran, 2009;Stahl et al, 2011). This data is valuable for conceptualization and theorizing, especially for studies which explore the behaviors of individuals as part of a social system (Belanger, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (e.g., Kitzinger, 1994) have advocated for the importance of capturing interaction data in groups through, for example, conducting unstructured sessions with acquaintances who have a unified goal but potentially different views (e.g., managers and administrators of an organization, teaching staff with prior interactions, and nurses at a department of a hospital). While some studies on the analysis of focus group method have emphasized the importance of analyzing both group level content and group interaction data (e.g., Grønkjaer et al, 2011;Kitzinger, 1994;Onwuegbuzie et al, 2009;Smithson, 2000;Stahl et al, 2011;O'hEocha et al, 2012), no study has suggested a systematic procedure of analyzing these two types of data in an integrated way. Such lack of a detailed and systematic procedure of analyzing focus group data may explain the paucity of IS research papers and doctoral dissertations that report group-level content data and interaction data from focus groups.…”
Section: Introductionmentioning
confidence: 99%